2018
DOI: 10.2147/ccid.s157297
|View full text |Cite
|
Sign up to set email alerts
|

Skin acceptability of a cosmetic moisturizer formulation in female subjects with sensitive skin

Abstract: PurposeThis 3-week, open-label, noncomparative clinical study evaluated the skin acceptability of a cosmetic moisturizer in subjects with sensitive skin, by monitoring adverse events (AEs) and cutaneous discomfort related to normal usage.Materials and methodsFemale subjects aged between 18–60 years, with Fitzpatrick phototype classification I–IV and sensitive skin, verified by a positive reaction on the stinging test at screening, were included. Subjects applied the moisturizer to their face and body twice dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
0
9
0
2
Order By: Relevance
“…In this regard, moisturizers containing functional ingredients such as endocannabinoids and based on the principles of biomimic technology are gaining increasing importance 21–25 . The endocannabinoid system (ECS) balances and regulates the proliferation, differentiation, and survival of skin cells and is thus believed to play an active role in protective mechanisms in skin barrier function 26 .…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, moisturizers containing functional ingredients such as endocannabinoids and based on the principles of biomimic technology are gaining increasing importance 21–25 . The endocannabinoid system (ECS) balances and regulates the proliferation, differentiation, and survival of skin cells and is thus believed to play an active role in protective mechanisms in skin barrier function 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Skin hydration is closely related to the moisture content of the stratum corneum, which is the outermost layer of the epidermis. The stratum corneum has an organic complex structure of proteins and lipids that forms the skin barrier; a decrease in the moisture content of the stratum corneum results in dryness of the skin and abnormalities in skin barrier function (Nisbet, 2018). Furthermore, the main role of ceramide in the stratum corneum is protecting the epidermal barrier, and a decrease in the ceramide content in the stratum corneum weakens the skin barrier function and acts as a cause of increased water loss between the skin.…”
Section: Discussionmentioning
confidence: 99%
“…These two products in this study used on subjects with AD were both concluded to be cutaneously acceptable by the dermatologist investigator Table A1 ( Appendix A ). Although some reactions were noted, it can be concluded that these are quite normal when using such products on subjects with such a condition, and can occur in some individuals with sensitive skin when applying new products [ 50 ]. We can observe from these results that L. reuteri DSM 17938 as an additive ingredient to the topical ointment does not affect the cosmetic or cutaneous acceptability of the product.…”
Section: Discussionmentioning
confidence: 99%